Domperidone for Delayed Gastric Emptying in Lung Transplant Recipients with and without Gastroesophageal Reflux. (March 2014) - Lidor, Anne O.; Ensor, Christopher R.; Sheer, Amy J.; Orens, Jonathan B.; Clarke, John O.; McDyer, John F.
Evidence demonstrates a link between gastroesophageal reflux disease and chronic allograft dysfunction in lung transplant recipients. Delayed gastric emptying plays an important role in the occurrence of gastroesophageal reflux disease, with limited therapeutic options available for treatment. This retrospective observational study reports the use of domperidone in the management of delayed gastric emptying in lung transplant recipients. All patients who underwent lung transplant at our institution from 2007 to 2011 were reviewed and patients who were treated with domperidone were identified. Clinical symptoms and results of gastric emptying studies before and after initiation of domperidone were documented. QTc intervals were compared from before to after domperidone treatment at 3 months and at 1 year. Weight and dose-normalized calcineurin inhibitor troughs were evaluated before and 2 weeks after domperidone treatment was started. Of 82 patients, 24% (n = 20) had documented delayed gastric emptying and 35% (n = 29) had documented gastroesophageal reflux disease. Twelve of the 20 patients with delayed gastric emptying started treatment with domperidone. All patients responded symptomatically and 6 patients with gastric emptying studies before and after domperidone had documented improvement. No adverse effects were observed in any patients treated with domperidone. Results indicate that domperidone can be used safely and may improve symptoms related to delayed gastric emptying in lung transplant recipients.